Changes in Subcellular Distribution of n-Octanoyl or n-Decanoyl Ghrelin in Ghrelin-Producing Cells - Nishi, Yoshihiro; Mifune, Hiroharu; Yabuki, Akira; Tajiri, Yuji; Hirata, Rumiko; Tanaka, Eiichiro; Hosoda, Hiroshi; Kangawa, Kenji; Kojima, Masayasu (Frontiers in Endocrinology, 2013)
Background: The enzyme ghrelin O-acyltransferase (GOAT) catalyzes the acylation of ghrelin. The molecular form of GOAT, together with its reaction in vitro, has been reported previously. However, the subcellular processes governing the acylation of ghrelin remain to be elucidated. Methods: Double immunoelectron microscopy was used to examine changes in the relative proportions of secretory granules containing n-octanoyl ghrelin (C8-ghrelin) or n-decanoyl ghrelin (C10-ghrelin) in ghrelin-producing cells of mouse stomachs. The dynamics of C8-type (possessing C8-ghrelin exclusively), C10-type (possessing C10-ghrelin only), and mixed-type secretory granules (possessing both C8- and C10-ghrelin) were investigated after fasting for 48 h or after 2 weeks feeding with chow containing glyceryl-tri-octanoate (C8-MCT) or glyceryl-tri-decanoate (C10-MCT). The dynamics of C8- or C10-ghrelin-immunoreactivity (ir-C8- or ir-C10-ghrelin) within the mixed-type granules were also investigated. Results: Immunoelectron microscopic analysis revealed the co-existence of C8- and C10-ghrelin within the same secretory granules (mixed-type) in ghrelin-producing cells. Compared to control mice fed standard chow, the ratio of C10-type secretory granules increased significantly after ingestion of C10-MCT, whereas that of C8-type granules declined significantly under the same treatment. After ingestion of C8-MCT, the proportion of C8-type secretory granules increased significantly. Within the mixed-type granules the ratio of ir-C10-ghrelin increased significantly and that of ir-C8-ghrelin decreased significantly upon fasting. Conclusion: These findings confirmed that C10-ghrelin, another acyl-form of active ghrelin, is stored within the same secretory granules as C8-ghrelin, and suggested that the types of medium-chain acyl-molecules surrounding and available to the ghrelin-GOAT system may affect the physiological processes of ghrelin acylation.